TERMINOLOGIE ET TRADUCTION DES NANOSCIENCES ET NANOTECHNOLOGIES : DE L’ANGLAIS AUX LANGUES ROMANES - DINCĂ, Daniela; PREITE, Chiara (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Terminology and Translation of Nanoscience and Nanotechnologies: From English to Romance Languages. Based on our experience of building a Multilingual Nanoscience and Nanotechnology Glossary, we propose in this article to study the complementary relationship between the terminology of nanotechnology and its translation from English as a source language to the languages analyzed: French and, more particularly, Italian and Romanian. More specifically, the objectives set out in this contribution are to describe the terminology and definitions of nanoscience and nanotechnologies from the perspective of their translation in order to highlight the common and divergent elements among the three Romance languages: French, Italian and Romanian. Terminologie și traducerea nanoștiințelor și a nanotehnologiilor: din engleză în limbile romanice. Plecând de la experiența noastră în elaborarea unui Glosar multilingv de nanoștiințe și nanotehnologii, ne propunem să abordăm relația complementară care se stabilește între terminologia nanotehnologiei și traducerea acesteia din limba engleză, ca limbă sursă, în limbile franceză și, ulterior, italiană și română. Mai precis, obiectivele stabilite în acest articol sunt descrierea terminologiei și a definițiilor din domeniul nanoștiințelor și al nanotehnologiilor din perspectiva traducerii acestora, pentru a evidenția punctele comune și divergente între cele trei limbi romanice: franceză, italiană și română. Cuvinte-cheie: traducere tehnică, terminologie, procedee ale traducerii, nanotehnologie, definiție conceptuală Article history: Received 21 August 2023; Revised 15 December 2023; Accepted 31 January 2024; Available online 27 March 2024; Available print 27 March 2024.